2023
DOI: 10.3390/agronomy13030680
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Chemical Forms of Cadmium in Tissues of Different Vegetable Crops

Abstract: Large areas of arable lands in China have been contaminated by heavy metals, in which cadmium (Cd) contamination was the most prevalent. Cd accumulation in main food crops and leafy vegetables grown in Cd-contaminated fields has aroused considerable attention in recent years. The present study investigated the Cd pollution of farmland soils and vegetables in Qujing city of Yunnan Province, China. By comparing the Cd uptake capacities of different crops, this study aimed to provide guidance for agricultural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The present study showed that the leafy vegetable lettuce had higher a Cd enrichment capacity than root vegetables. Some previous studies showed that leafy vegetables were more likely to accumulate Cd than non-leafy vegetables [36], which is consistent with the results of the present study. The BAF was also affected by the bioavailability of elements in soil and their interactions.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that the leafy vegetable lettuce had higher a Cd enrichment capacity than root vegetables. Some previous studies showed that leafy vegetables were more likely to accumulate Cd than non-leafy vegetables [36], which is consistent with the results of the present study. The BAF was also affected by the bioavailability of elements in soil and their interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, the level of bioaccumulation of the TMTs followed the order Cd > Zn > Cu > Pb > Mn > Cr. Hyperaccumulation of Cd in leafy vegetables has been reported previously in leafy vegetables such as B. oleracea [59], Brassica campestris L., Brassica chinensis L. and Brassica juncea L. [60].…”
Section: Trace Metal Pollution Of Soils and Their Bioaccumulation In ...supporting
confidence: 52%
“…The study reported that the TF of elements from soil to plants differs, with the TF for Cd being greater than that of Cr and Pb [ 57 ]. Xiao et al [ 58 ] also found that the TF of Cd from root to leaf is higher than from root to stem [ 58 ].…”
Section: Resultsmentioning
confidence: 99%